Development of Anodic Oxidation Process and Boehmite Process in Production Process of Dehydrogenation Catalyst - Han, Chang-Suk; Seo, Han-Byeol (Asian Journal of Chemistry, 2016)
Organic hydride is anticipated for use as a future hydrogen carrier because it has both high gravimetric and volumetric hydrogen density for storage and transportation. Improving the performance of the dehydrogenation catalyst is necessary to miniaturize the reactor, which generates H2 from organic hydride in an endothermic reaction. The porous anodic oxide film on aluminum is widely known for its application to dehydrogenation catalysts. Increasing the specific surface area of a porous anodic oxide film improves the catalytic performance. For this study, we obtained a catalyst with high specific surface area by investigating the anodic oxidation temperature and boehmite process time. The specific surface area of a porous anodic oxide film produced at higher temperature was larger than that at a lower temperature. It increased with boehmite processing time. However, when the specific surface area became too large, the micropores were too small for Pt particles to enter. Consequently, at 50 °C anodic oxidation temperature and at about 5 h boehmite processing time, the catalyst had the most suitable specific surface area to generate H2 from methylcyclohexane because the smallest Pt particles were supported on the porous anodic oxide film. Furthermore, a microreactor using the proposed catalyst had twice the methylcyclohexane conversion as that using a conventional catalyst.